A case report of subglottic haemangioma - Karunakaran, Vignesh; Swamirao Rajaganesh, Kutuva; Natarajan, Dhinakaran (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
We report a case of 18 year old female who presented with hoarseness of voice and hemoptysis for 6 months eventually diagnosed as subglottic haemangioma through video laryngoscopy, CT imaging and histopathological examination of excision biopsy. The tumor excision was done by endolaryngeal surgery with tracheostomy under general anesthesia. The diagnosis of subglottic haemangioma, its management and prognosis were discussed.